FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KELUARGA PASANGAN USIA SUBUR DALAM MENENTUKAN JUMLAH ANAK DI DUSUN VII SUKAJADI KECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI TAHUN 2015 - Borus, Ernawati; Lumbantoruan, Mestika; Nakhera, Tari (UNIVERSITAS SARI MUTIARA INDONESIA, 2016)
Population issues are closely related, reproductive health services, among others, prenatal care and delivery assistance, how to reduce infant mortality and maternal mortality, For certain people assume that boys with perempuanmemiliki different socio-cultural values. They assume that boys will inherit his father's clan descent. The fact that many couples of childbearing age who live in Dusun VII Sukajadi there are some who live at home with parents, make a lot of decisions on the selection of health care is fertile couples in the intervention by parents, including when the fertile couples or a family planning program no. The aim of research to determine the factors that influence family decisions couples of childbearing age in determining the number of children in DesaSukajadiKecamataDolokMasihul Year 2015. Methods of survey with explanatory research approach that aims to explain the influence of the independent variables through statistical analysis. The population in this study were married couples of childbearing age in Dusun VII Sukajadi, 150 pairs. The sample was the wife of couples of reproductive age are as many as 60 people. There are research results influence intention, community support, information, situation on compliance pair Eligible families in determining the number of children and there was no effect on adherence autonomy pair Eligible families in determining the number of children, variables that influence adherence pair Eligible families in determining the number of children is variable community support. KB SKPD suggestions can improve outreach to the community about the importance of planning in the determination of the number of children that either through brousur, leflat andother media lektronik The family planning program to support both the head of the family, the parents in order to support the wife is unable to implement the family planning program.